Current understanding of the diagnosis and management of the tendinopathy: An update from the lab to the clinical practice - Canosa-Carro, Lorena; Bravo-Aguilar, María; Abuín-Porras, Vanesa; Almazán-Polo, Jaime; García-Pérez-de-Sevilla, Guillermo; Rodríguez-Costa, Isabel; López-López, Daniel; Navarro-Flores, Emmanuel; Romero-Morales, Carlos (Disease-a-month, 2022)
Tendinopathy is labeled by many authors as a troublesome, common pathology, present in up to 30% medical care consultations involving musculoskeletal conditions. Despite the lasting interest for addressing tendon pathology, current researchers agree that even the exact definition of the term tendinopathy is unclear. Tendinopathy is currently diagnosed as a clinical hypothesis based on the patient symptoms and physical context. One of the main goals of current clinical management is to personalize treatment approaches to adapt them to the many different needs of the population. Tendons are complex structures that unite muscles and bones with two main objectives: to transmit forces and storage and release energy. Regarding the tensile properties of the tendons, several authors argued that tendons have higher tensile strength compared with muscles, however, are considered less flexible. Tendinopathy is an accepted term which is used to indicated a variety of tissue conditions that appear in injured tendons and describes a non-rupture damage in the tendon or paratendon, which is intensified with mechanical loading Even when the pathoetiology of tendinopathy is unclear, there is a wide array of treatments available to treat and manage tendinopathy. Although tendinitis usually debuts with an inflammatory response, the majority of chronic tendinopathies do not present inflammation and so the choosing of treatment should vary depending on severity, compliance, pain and duration of symptoms. The purpose of this article is to review and provide an overview about the currently research of the tendon diagnosis, management and etiology.